The Relationship between Zinc Levels and Autism: A Systematic Review and Meta-analysis - BABAKNEJAD, Nasim; SAYEHMIRI, Fatemeh; SAYEHMIRI, Kourosh; MOHAMADKHANI, Ashraf; BAHRAMI, Somaye (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Babaknejad N, Sayehmiri F, Sayehmiri K, Mohamadkhani A, Bahrami S. The Relationship between Zinc Levels and Autism: Systematic Review and Meta-analysis. Iran J Child Neurol. Autumn 2016; 10(4):1-9. Abstract Objective Autism is a complex behaviorally defined disorder. There is a relationship between zinc (Zn) levels in autistic patients and development of pathogenesis, but the conclusion is not permanent. Materials & Methods The present study conducted to estimate this probability using meta-analysis method. In this study, Fixed Effect Model, twelve articles published from 1978 to 2012 were selected by searching Google scholar, PubMed, ISI Web of Science, and Scopus and information were analyzed. I² statistics were calculated to examine heterogeneity. The information was analyzed using R and STATA Ver. 12.2. Results There was no significant statistical difference between hair, nail, and teeth Zn levels between controls and autistic patients: -0.471 [95% confidence interval (95% CI): -1.172 to 0.231]. There was significant statistical difference between plasma Zn concentration and autistic patients besides healthy controls: -0.253 (95% CI: 0.498 to -0.007). Using a Random Effect Model, the overall Integration of data from the two groups was -0.414 (95% CI: -0.878 to -0.051). Conclusion Based on sensitivity analysis, zinc supplements can be used for the nutritional therapy for autistic patients. References 1. Arnold LE, Farmer C, Kraemeret HC, et al. Moderators, mediators, and other predictors of Risperidoneresponse in children with Autistic Disorder and Irritability. J Child Adolesc Psychopharmacol 2012; 20(2): 83-92. 2. Karimzadeh P. Recent finding about etiology of autism. Rehabilitation 2000; 1(2):58-63. 3. Dufault R, Schnoll R, Lukiw WJ, et al. Mercury exposure, nutritional deficiencies and metabolic disruptions may affect learning in children. Behav Brain Funct 2009; 5(44): 1-15. 4. Morris CR, Agin CM. Syndrome of allergy, apraxia, and malabsorption: characterization of a neurodevelopmental phenotype that responds to omega 3 and vitamin E supplementation. Altern Ther Health Med 2009; 15(4): 34-43. 5. An centers for Disease Control and Prevention (2012). Prevalence of autism spectrum disorders-Autism and Developmental Disabilities Monitoring Network, Prevalence of Autism Spectrum Disorders (ASDs) Among Multiple Areas of the United States in 2008, United States, Morbidity and Mortal Weekly Report (MMWR); Vol. 61(3). 6. Dufault R, Lukiw WJ, Crider R, et al. A macro epigenetic approach to identify factors responsible for the autism epidemic in the United States. Clin Epigenetics 2012; 4(6): 2-12. 7. Faber S, Zinn GM, Kern GC, et al. The plasma zinc/ serum copper ratio as a biomarker in children with autism spectrum disorders. Biomarkers 2009; 14(3): 171–180. 8. Cornish E. Gluten and casein free diets in autism: a study of the effects on food choice and nutrition. J Hum Nutr Dietet 2012; 15: 261-268. 9. De Palma G, Catalani S, Franco A, et al. Lack of correlation between metallic elements analyzed in hair by ICP-MS and Autism. J Autism Dev Disord 2012; 42(3):342–353. 10. Adams JB, Romdalvik J, Ramanujam VM, Legator MS, et al. Mercury, Lead, and Zinc in Baby teeth of children with Autism versus controls. J Toxicol Environ Health A 2007;7(12): 1046-1051. 11. Blaurock-Busch E, Amin OR, Rabah T. Heavy metals and Trace elements in hair and urine of a sample of Arab children with Autistic Spectrum Disorder. Maedica (Buchar) 2011;6(4): 247-252. 12. Russo AJ, Devito R. Analysis of Copper and Zinc Plasma Concentration and the efficacy of Zinc therapy in individuals with Asperger’s syndrome, pervasive Developmental Disorder Not Otherwise Specified (PDDNOS) and Autism. Biomarker Insights 2011; 6:127–133. 13. Shearer TR, Larson K, Neuschwander J, Gedney B. Minerals in the hair and nutrient intake of Autistic children. J Autism Dev Disord 1982; 12(1): 25-30. 14. Liberati A, Tetzlaff J, Mulrow C, et al. The PRISMA statement for reporting systematic reviews and metaanalyses of studies that evaluate healthcare interventions: explanation and elaboration. BMJ 2009; 21: 339- b2700. 15. Hartung J, Knapp G, Sinha BK. Statistical Meta- analysis with application. John Willey and Sons 2008, INC, USA. 16. Babaknejad N, Sayehmiri F, Sayehmiri K, et al. The relationship between selenium levels and breast cancer: a systematic review and meta-analysis. Biol Trace Elem Res 2014;159(1-3):1-7. 17. Al-Ayadehi LY. Heavy metals and trace elements in hair samples of autistic children in central Saudi Arabia. Neurosciences (Riyadh) 2005; 10(3):213-8. 18. Blaurock-Busch E, Amin OR, Dessoki HH, Rabah T. Toxic metals and essential elements in hair and severity of symptoms among children with Autism. Mædica J Clin Med 2012;7(1): 38-47. 19. Elsheshtawy E, Tobar S, Sherra K, et al, Study of some biomarkers in hair of children with autism. MECPsych 2011;18 18:6–10. 20. Russo AJ. Increased Copper in individuals with Autism normalizes post Zinc therapy more efficiently in Individuals with in current GI Disease. Nutr Metab Insights 2011;4: 49–54. 21. Jackson MJ, Garrod PJ. Plasma Zinc, Copper, and Amino Acid levelsin the blood of Autistic Children. J Autism Child Schizophr 1978; 8(2): 203-206. 22. Priya MDL, Geetha A. Level of trace elements (Copper, Zinc, Magnesium and Selenium) and toxic elements (Lead and Mercury)in the Hair and Nail of Children with Autism. Biol Trace Elem Res 2011; 142(2): 148–158. 23. Wecker L, Miller SB, Cochran SR, Dugger DL, Johnson WD. Trace element concentrations in hair from autistic children. J Ment Defic Res 1985; 29(1): 15-22. 24. Adams JB, Audhya T, McDonough-Means S, et al. Nutritional and metabolic status of children with autism vs. neurotypical children, and the association with autism severity. Nutr Metab (Lond) 2011; 8(34): 1-30. 25. Adams JB, Holloway CE, George F, Quig D. Analyses of toxic metals and essential minerals in the hair of Arizona Children with Autism and associated conditions, and their mothers. Biol Trace Elem Res 2006; 110: 194-207. 26. Al-Farsi YM, Waly MI, Al-Sharbati MM, et al. Levels of heavy metals and essential minerals in hair samples of children with Autism in Oman: a Case–Control Study. Biol Trace Elem Res 2013;151(2): 181-6. 27. Russo AJ. Decreased serum Cu/Zn SOD in children with Autism. Nutr Metab Insights 2009; 2: 27-35. 28. Xia W, Zhou Y, Sun C, Wang J, Wu L. A preliminary study on nutritional status and intake in Chinese children with autism. Eur J Pediatr 2010; 169(10):1201-1205. 29. Russo AJ, Bazin AP, Bigega R, et al. Plasma Copper and Zinc Concentration in Individuals with Autism Correlate with Selected Symptom Severity. Nutr Metab Insights 2012;5: 41–47. 30. Bjørklund G. The role of zinc and copper in autism spectrum disorders. Acta Neurobiol Exp 2013; 73: 225–236. 31. Yasuda H, Yoshida K, Yasuda Y, Tsutsui T. Infantile zinc deficiency: Association with autism spectrum disorders. Sci Rep 2011; 1(129): 1-4. 32. Frye RE, Rossignol D2, Casanova MF, et al. A review of traditional and novel treatments for seizures in autism spectrum disorder: findings from a systematic review and expert panel. Front Public Health 2013; 1(31): 1-17. 33. Yasuda H, Tsutsui T. Assessment of Infantile Mineral Imbalances in Autism Spectrum Disorders (ASDs). Int J Environ Res Public Health 2013;10(11): 6027–6043.